Power, trust and relationship commitment in dealer-supplier relationship in Thailand automobile industry - Pourpunsawat, Pakorn; Mohd Noor, Nor Azila; Romle, Abd Rahim (IDOSI Publications, 2017)
The automotive industry is one of the main industries in Thailand with significant contribution to the economy, employment, value added and automotive technology development in Thailand as well as supply chain related industries. The automotive industry is one of the main industries in Thailand that generates economic value for the country. Due to consistent economic and industrial growth in Thailand and Asia, in 2014, Thailand automotive production capacity manage to exceed 3 million vehicles each for automobile and motorcycles. The concept of relationship commitment between buyers and sellers has generated lot of interests and has been the central focus in relationship marketing research. The purpose of this study is to examine the power influence in the relationship commitment between dealers and suppliers in the Thai automobile industry.